Trilhas da acessibilidade e inclusão de pessoas com paralisia cerebral no ensino médio integrado : percursos da comunidade acadêmica - Moro, Tatiele Bolson (My University, 2023)
This thesis addresses inclusive education in vocational education during the Covid 19 pandemic and seeks to articulate continuing education, experiences, planning, collaboration, and pedagogical practices, focusing on the learning and development of students with cerebral palsy, but primarily as a movement to transform subjects. The aim of this research is to analyze how the articulations and solutions carried out by the school community in relation to inclusion and accessibility are composed in a process of collective reflection and construction aimed at pedagogical actions for students with cerebral palsy in the context of the Integrated Secondary School in times of pandemic. Therefore, the theoretical framework is supported by studies on disability models, inclusive education, continuing education in context, accessibility, experiences, cerebral palsy, universal design for learning, and assistive technology. The research is qualitative in nature and uses action research as the design (THIOLLENT, 2007; BRAUN, 2020). As data construction, we conducted procedures such as semistructured interviews, accessibility trails (reflection and discussion meetings), and pedagogical actions (moments of planning and developing activities). Five teachers of vocational schools, three administrative technicians in education and two students with cerebral palsy associated with a federal institute participated in the research. The search with was the way to research by constructing the search in a common way. The data were analyzed considering Bardin's (2016) content analysis using qualitative data analysis software ATLAS.ti. The research was divided into different phases: a) initial phase, in which the interviews of phase 1 were conducted, from which the categories of educational practices and schooling, pathways and gaps, and understanding and experiences emerged; b) action phase, in which the accessibility pathways and pedagogical actions were carried out, where in the first phase reflection and discussion meetings were held on topics such as inclusion, accessibility, planning, autonomy, etc. took place; in the second phase, pedagogical activities were carried out in collaboration; c) evaluation phase, in which the interviews of phase 2 were conducted. From the analysis, the following categories emerged: Pedagogical Practices and Schooling; Pathways and Gaps in Teaching; Understanding and Experiences; and Reflections on Research. From the analysis movement, it can be inferred that from the perspective of inclusive pedagogy in professional education, special education needs to focus on the articulation of CPD in context and collaboration that allows for "experiences" between teachers, technicians, and students to transform subjects. It is noteworthy that CPD in context, along with DUA and the SETT framework, has contributed to the construction of pedagogical practices, the definition of problems, and the construction of alternative solutions, resulting in subjects moving in ways that reshape themselves. From the analysis movement, it can be deduced that from the perspective of inclusive education in vocational education, special education must focus on the articulation of CPD in the context and collaboration that allow "experiences" between teachers, technicians and students to transform the subjects. It is noteworthy that CPD in context, along with DUA and the SETT framework, has contributed to the construction of pedagogical practices, the definition of problems and the construction of alternative solutions that lead the movement of subjects in a way that they transform themselves. [resumo fornecido pelo autor]
Esta Tese aborda sobre Educação Inclusiva no ensino profissionalizante durante o período de pandemia por Covid-19, buscando articular a formação continuada, as vivências, os planejamentos, o trabalho colaborativo e as práticas pedagógicas com o foco na aprendizagem e no desenvolvimento do estudante com Paralisia Cerebral, mas principalmente como um movimento para a transformação dos sujeitos. O objetivo desta pesquisa é o de analisar como se compõem as articulações e as soluções realizadas pela comunidade escolar em relação à inclusão e à acessibilidade, em processo de reflexão e construção conjuntas, voltadas para ações pedagógicas aos alunos com Paralisia Cerebral no contexto do Ensino Médio Integrado, em tempos de pandemia. Para tanto, o referencial teórico está apoiado nos estudos sobre modelos de deficiência, educação inclusiva, formação continuada em contexto, acessibilidade, vivências, paralisia cerebral, desenho universal para a aprendizagem e tecnologia assista. A pesquisa é de natureza qualitativa, adotandose como delineamento a pesquisa-ação (THIOLLENT, 2007; BRAUN, 2020) e como procedimentos de construção dos dados as foram realizadas entrevistas semiestruturadas, Trilhas de Acessibilidade (encontros de reflexão e discussão) e Ações Pedagógicas (momentos de planejamento e desenvolvimento de atividades). Participaram da pesquisa cinco docentes dos cursos profissionalizantes, três técnicos administrativos em educação e dois estudantes com paralisia cerebral vinculados a um Instituto Federal. O pesquisar com foi a forma de pesquisar construindo o pesquisar de forma compartilhada. Os dados foram analisados considerando a Análise de Conteúdo, de Bardin (2016), com o auxílio do software de análise qualitativa de dados ATLAS.ti. A pesquisa foi dividida em etapas: a) Etapa Inicial, na qual foi realizada as entrevistas da Fase 1, e a partir desta emergiram as categorias práticas educacionais e escolarização; caminhos e lacunas e; compreensões e vivências; b) Etapa de Ação foram realizadas as Trilhas de Acessibilidade e Ações Pedagógicas, na primeira foram realizados encontros de reflexão e discussão sobre temas como inclusão, acessibilidade, planejamento, autonomia, entre outros; no segundo foram realizadas atividades pedagógicas de forma colaborativa; c) Etapa de Avaliação foi realizada as entrevistas da Fase 2. A partir da análise emergiram as categorias: Práticas educacionais e escolarização; Caminhos e lacunas no ensino; Compreensões e vivências e Reflexões sobre a pesquisa. O movimento de análise permitiu inferir que a Educação Especial na perspectiva da Educação Inclusiva no ensino profissionalizante deve contar com a articulação da formação continuada em contexto e do trabalho colaborativo, que possibilitem ?vivências? entre professores, técnicos e estudantes, de modo a transformar os sujeitos. Destaca-se que a formação em contexto, em conjunto com o DUA e Framework SETT, contribuiu na construção de práticas pedagógicas, na definição de problemáticas e na construção de soluções alternativas, conduzindo o movimentar dos sujeitos de forma que se refaçam. [resumo fornecido pelo autor]
Keywords: Educação inclusiva; Ensino médio; Inclusão escolar; Paralisia cerebral - Educação; Aprendizagem; Inclusive education; High school; Mainstreaming in education; Cerebral palsy - Education; Learning